2020
DOI: 10.1038/s41380-020-00898-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals new insights into the heritability and genetic correlates of developmental dyslexia

Abstract: Developmental dyslexia (DD) is a learning disorder affecting the ability to read, with a heritability of 40–60%. A notable part of this heritability remains unexplained, and large genetic studies are warranted to identify new susceptibility genes and clarify the genetic bases of dyslexia. We carried out a genome-wide association study (GWAS) on 2274 dyslexia cases and 6272 controls, testing associations at the single variant, gene, and pathway level, and estimating heritability using single-nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 105 publications
4
76
1
Order By: Relevance
“…Indeed, a genetic link may have not been detected due to other (possibly rare or structural) genetic variants being at the basis of this. This hypothesis has been supported by recent findings for other complex traits like general cognition, educational attainment ( 28 ), and dyslexia ( 29 ), where only half of the heritability has been explained by common SNPs. Even so, this study rules out any large genetic overlap between PDW and AD risk.…”
Section: Resultsmentioning
confidence: 56%
“…Indeed, a genetic link may have not been detected due to other (possibly rare or structural) genetic variants being at the basis of this. This hypothesis has been supported by recent findings for other complex traits like general cognition, educational attainment ( 28 ), and dyslexia ( 29 ), where only half of the heritability has been explained by common SNPs. Even so, this study rules out any large genetic overlap between PDW and AD risk.…”
Section: Resultsmentioning
confidence: 56%
“…Consequently, longitudinal studies are needed to address this issue. Fourth, the markers that we selected for our study were not found to be associated with DD-related traits by GWAS [ 6 , 7 , 8 , 9 ] and in a large cross-linguistic sample [ 10 ]. The fact that GWAS did not confirm findings from association studies does not necessarily imply that previously reported associations were due to low statistical power and chance findings.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to earlier descriptions of high familial aggregation of DD [ 4 ], substantial heritability typical of a complex trait has been reported [ 5 ]. Although they have not been found to be associated with DD-related traits by recent GWAS [ 6 , 7 , 8 , 9 ] and in a large cross-linguistic sample [ 10 ], nine genes have been replicated in at least one independent sample by candidate genes studies: DYX1C1 , DCDC2 , KIAA0319 , C2orf3 , MRPL19 , ROBO1 , FAM176A , NRSN1 , KIAA0319L and FMR1 [ 11 ]. In our previous studies, we reported the association of single nucleotide polymorphisms (SNPs) spanning the DYX1C1 , DCDC2 , KIAA0319 , ROBO1 , and GRIN2B genes with DD and DD-related quantitative traits in Italian nuclear families with DD [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These behavioral symptoms can originate from deficits at the cognitive level, such as poor phonological processing [20,21], reduced processing speed [22,23], or deficits in working memory [22,[24][25][26]. The cognitive deficits may in turn be caused by factors at the biological level, which may for example include genetic factors [13,27], or brain structure and function [28][29][30]. Finally, the environmental level continuously influences and modifies the other three levels and comprises conditions such as the educational level of parents and other socio-economic factors [31,32], or school practices and learning environment [33].…”
Section: Introductionmentioning
confidence: 99%